SOCIALLY RESPONSIBLE MARKETING IN THE AGRICULTURAL SPHERE: PRACTICAL ASPECTS - Kubrak, N. R.; Sagan, V. R.; Solodukha Z. І. (The actual problems of regional economy development, 2024)
This article conducts a study on socially responsible marketing (SRM) practices adopted by enterprises in the agrarian sector. Grounded in the principles of sustainable development, SRM enables enterprises to strike a balance between profitability and consideration for social, environmental, and ethical aspects in their operations. Central to SRM is the notion of a balanced approach that considers the interests of consumers, society, and the environment. The spectrum of socially responsible marketing encompasses environmental, ethical, charitable, and financial dimensions. Regardless of whether a business adopts one or multiple types of CSR practices, it is likely to garner increased interest from customers, employees, and investors. The article argues that socially responsible marketing fosters the enhancement of brand reputation by employing ethical and sustainable marketing strategies. This underscores the priority of honesty and social responsibility, distinguishes the company from competitors, and attracts customers who value ethical business conduct. The authors employed inductive and deductive methods in writing the article. Through analysis and comparison, the study evaluates and contrasts socially responsible programs in Ukraine. The abstract-logical method is employed for theoretical generalizations and drawing conclusions. The article underscores the well-founded advantages of socially responsible marketing for enterprises, including image enhancement, increased social initiative, and heightened customer engagement. Notably, Ukraine boasts several successful examples of socially responsible marketing in the agricultural sector, with companies actively implementing sustainable development strategies and social responsibility initiatives. Prominent among these enterprises are MHP (Myronivskyi Khliboprodukt), AgroGeneration, and Agroprosperis Group. These companies exemplify how agricultural enterprises in Ukraine can embrace social responsibility and contribute to sustainable development while achieving their business objectives. The programs initiated by these enterprises span the entire country and provide assistance in various regions as needed.